Numerical analysis and theoretical calculation of tensile membrane action region of RC simply supported slabs under fire - Jia, Yan; Yang, Qi; Wang, Shanshan; Yu, Da; Teng, Fei; Yuan, Yuhui; Guo, Gengwen (Frontiers in Built Environment, 2026)
Tensile membrane action (TMA) could significantly enhance the ultimate bearing capacity of reinforced concrete (RC) simply supported slabs under fire conditions. To address this, this paper proposes an analytical method for determining the ultimate bearing capacity of RC slabs at elevated temperatures by explicitly accounting for the influence of TMA. In this method, the TMA region is reasonably defined via equations for an elliptical boundary, and the coefficient of increase in ultimate load‐carrying capacity is derived. Through a combination of fire testing, numerical analysis, and theoretical calculations, the study investigated the TMA region and the increase in the ultimate bearing capacity, revealing that temperature changes have little effect on the geometry and size of the TMA region. Furthermore, upon comparing three failure criteria to validate the accuracy of calculations, it was found that a deflection limit of w = l/10 provided good agreement, thereby facilitating further analysis of the ultimate load‐carrying capacity of simply supported slabs.